Challenges of women refugees in utilising reproductive health services in public health institutions in Durban, KwaZulu-Natal, South Africa - Yvonne Munyaneza; Euphemia M. Mhlongo (AOSIS, 2019)
Background: Reproductive health services are essential for everyone worldwide. In South Africa, the available literature does not address reproductive health as a full package for women refugees and their experiences. This study addressed women refugees in relation to reproductive healthcare services they receive from public healthcare facilities. Aim: The aim of the study was to document the day-to-day experiences of women refugees and uncover their challenges regarding utilisation of reproductive health services in public institutions of Durban, KwaZulu-Natal. Setting: The study was conducted in eThekwini district, Durban, KwaZulu-Natal, and did not consider participants who are located beyond the above-mentioned city's borders. Methods: A qualitative, descriptive design was used. A semi-structured interview guide was used to collect data through face-to-face in-depth interviews with eight women refugees. Thematic content analysis guided the study. Results: Two major themes emerged: negative experiences or challenges, and positive experiences. The most dominant negative experiences included medical xenophobia and discrimination, language barrier, unprofessionalism, failure to obtain consent and lack of confidentiality, ill-treatment, financial challenges, internalised fear, religious and cultural hegemony, and the shortage of health personnel and overcrowding of public hospitals. The positive experiences included positive treatment and care and social support. Conclusion: The findings revealed that women refugees in Durban, KwaZulu-Natal, face many challenges such as medical xenophobia and discrimination in their attempt to seek reproductive health services in public healthcare facilities, making them even more vulnerable. Assisting women refugees with their reproductive health needs will remediate the challenges they face.